2020
DOI: 10.1186/s12885-020-6681-2
|View full text |Cite
|
Sign up to set email alerts
|

An unusual hematopoietic stem cell transplantation for donor acute lymphoblastic leukemia: a case report

Abstract: Background: Donor acute lymphoblastic leukemia with recipient intact is a rare condition. We report a case of donor developing acute lymphoblastic leukemia 8 yrs after donating both bone marrow and peripheral blood hematopoietic stem cells. Case presentation: This case report describes a 51-year old female diagnosed with acute lymphoblastic leukemia who donated both bone marrow and peripheral blood stem cells 8 yrs ago for her brother with severe aplastic anemia. Whole exome sequencing revealed leukemic geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The most effective leukemia treatments still rely on conventional, low-specificity chemotherapy followed by HCT (Cornelissen et al, 2016;Zhou et al, 2020). Importantly, HCT treatment requires immunosuppressive drugs increased risk of life-threatening microbial infections (Poutsiaka et al, 2007).…”
Section: Current Knowledgementioning
confidence: 99%
“…The most effective leukemia treatments still rely on conventional, low-specificity chemotherapy followed by HCT (Cornelissen et al, 2016;Zhou et al, 2020). Importantly, HCT treatment requires immunosuppressive drugs increased risk of life-threatening microbial infections (Poutsiaka et al, 2007).…”
Section: Current Knowledgementioning
confidence: 99%
“…Even short‐term prophylactic G‐CSF in chemotherapy patients is now reported to synergistically enhance chemotherapy‐related risks for a secondary myeloid leukemia 4,5 . Among related HPC donors, there are rare reports of cancer occurring years after G‐CSF mobilization possibly reflecting familial genetic risk factors 6,7 . Studies by National Marrow Donor Program (NMDP), however, have shown no increased risk of cancer in healthy donors 2 .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Among related HPC donors, there are rare reports of cancer occurring years after G-CSF mobilization possibly reflecting familial genetic risk factors. 6,7 Studies by National Marrow Donor Program (NMDP), however, have shown no increased risk of cancer in healthy donors. 2 We now report an unusual case of G-CSF unmasking and mobilizing a new therapy-related acute lymphocytic leukemia (t-ALL) in a young male with a testicular embryonic germ cell tumor undergoing autologous HPC collection (HPCC).…”
Section: Introductionmentioning
confidence: 99%